The CPS Workers’ Child Removal Decision in Cases of Domestic and Witnessed Violence - Milani, Luca (Journal of interpersonal violence, 2023)
This study aimed to explore maternal and paternal risks and protective factors that may influence the Child Protection Service (CPS) workers’ child removal decision in case of domestic and witnessed violence. In all, 218 case reports of Italian CPSs were retrospectively analyzed through the Protocol of Risk and Protective Factors. The sample was then split up into two groups on the basis of the CPS professionals’ placement decision after the investigation (child removal decision versus parents support and monitoring intervention). Two statistical approaches were used to identify the patterns of risk and protective factors associated with maternal and paternal assessments: logistic regression models and decision tree analysis. Results showed that mothers who are victims of Intimate Partner Violence experienced the child removal in about half of the cases, while fathers showed a higher removal rate. Differences emerged between mothers’ and fathers’ risk profiles, suggesting that workers attributed a different weight to some factors depending on whether they concerned the mother or the father. Only the proximal risk factor poor empathy skills was significant for both mothers and fathers. For the mothers’ group, one of the most important factors was the presence of direct forms of child maltreatment in addition to witnessed violence, while for fathers’ group the drug abuse emerged a crucial relevant proximal risk factor.